Molecular Imaging of Cardiovascular Disease - Verjansr, J.; Hofstra, L. (SA Heart Journal, 2017)
The ability to visualize morphology and function of the heart plays a central role in cardiology practice today. However, clinical tools to diagnose processes in an early phase on a molecular level in order to prevent dysmorphy or dysfunction are still lacking. There is a need for early diagnosis of molecular processes on a pre-disease level and the ability to monitor existing and novel treatments enabling personalized medicine. Molecular imaging is emerging in research and early clinical trials as a very promising approach in diagnosis and monitoring of heart disease. In this review we aim to discuss the potential of molecular imaging in cardiovascular disease.